AI literacy of pre-service English teachers: Proficiency, strategies, and barriers - Febriyanti; Eva Nurchurifiani; Tommy Hastomo; Andri Wicaksono; Sukma Septian Nasution (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2026)
Artificial intelligence (AI) has become increasingly significant in higher education, making multidimensional AI literacy essential for pre-service English teachers. Yet, empirical evidence in English Language Teaching (ELT) remains limited, particularly regarding students’ AI literacy profiles, the autonomous strategies they use to develop such literacy, and the barriers affecting responsible AI use. This study employed an explanatory sequential mixed-method design in Indonesia. Quantitative data were collected through a 30-item AI literacy questionnaire administered to 200 pre-service English teachers, followed by semi- structured interviews and focus group discussions with a purposive subsample of 25 participants. The findings indicate an uneven AI literacy profile. Although participants demonstrated strong competence in the practical use of AI tools, they showed weaker performance in higher-order dimensions, especially evaluative and ethical aspects. The qualitative data further revealed that students developed AI literacy through self-directed strategies such as prompt experimentation and output verification, but these efforts were constrained by limited institutional guidance and persistent ethical uncertainty. The study suggests that teacher education programs should incorporate structured AI literacy instruction supported by clear institutional policies to strengthen critical, reflective, and responsible AI engagement in ELT contexts.